Afocal Mirror Systems with Small Axial Dimensions - N. K. Artioukhina (Pribory i Metody Izmerenij, 2020)
The searching and designing new solutions for mirror systems, including afocal ones, has been studied for decades. In the design, it has always been difficult to combine optimization and cost. Nowadays, the problem remains relevant. The widespread use of mirror systems is due to some aspects: thermal stability, high resolution in a wide spectral range, and the absence of image defects due to chromatic aberrations. All this provides superior performance compared to lens systems. The purpose of this paper is the design of two compact afocal mirror systems with small axial dimensions.Schemes of afocal three mirror systems with small axial dimensions are presented. The schemes can also be called compacts. A study was made of systems in which the diameter of the aperture diaphragm in the primary mirror is modified, which leads to a more compact system.A calculation algorithm of new the systems is proposed, with correction of the image curvature. A summary of formulas of the main parameters of the system is given, and various design solutions are calculated for angular field of view 2ω = 20ˈ and diameter of the entrance pupil D = 35 and D = 70 mm.Computer simulations were performed in the Opal, Zemax, and Code V software. The designed systems have good correction of aberrations for the given characteristics: in the spot diagrams, the values of the RMS scatter spot do not exceed 1,35 μm; GEO radius (distance from the reference point) – 0.105 μm; together with Airy disk sizes of about 9.16 μm, indicating that the images are close to diffraction.The calculated systems can be successfully applied as part of a more complex system, as well as in systems with a synthesized aperture.